POLYPHENOLS AND ANTIOXIDANT ACTIVITY OF THE HYDROALCOHOLIC EXTRACT OF PETROSELINUM CRISPUM (MILL) FUSS LEAVES AND ITS APPLICATION IN A DERMOCOSMETIC CREAM - Rojas Valdivia, Jorge (2023)
Petroselinum crispum (Mill) Fuss is an aromatic herb that contains various phytochemical compounds in its aerial parts, among which polyphenols stand out; likewise, it is attributed antioxidant property. The objective was to evaluate the content of phenolic compounds, the antioxidant activity of the hydroalcoholic extract of Petroselinum crispum (Mill) Fuss and the preparation of a dermocosmetic cream. The determination of polyphenols was carried out applying the in vitro method of Folin Ciocalteu and; the uptake of free radicals, by the DPPH• and ABTS•+ methods. The hydroalcoholic extract obtained a yield of 3.94 % and through a phytochemical screening the presence of phenolic compounds, flavonoids, terpenes, lactones and anthraquinones was confirmed. The following results were obtained: 4.33 ± 0.0162 mg EAG/g of phenolic compounds and TEAC-DPPH• and ABTS•+ values of 6.4322 mg Trolox®/g and 40.8511 mg Trolox®/g of extract, respectively. The IC50 values were 396.27 and 111.53 μg/ml, (p < 0.05). The extract presented low antioxidant activity compared to the Trolox® standard. Dermocosmetic creams were made with the hydroalcoholic extract of Petroselinum crispum (Mill) Fuss at concentrations of 1%, 2% and 4%. It was confirmed that the antioxidant activity was maintained for the intermediate concentration cream (2%), with a TEAC = 1.05 mg Trolox®/g 2% cream. Presenting significant differences between the 1%, 2% and 4% concentration creams, applying the Tukey method with a confidence level of 95% (p ≤ 0.05).